Periodic Modeling of Air Temperature Dynamics Across Four Regions of Lombok Island Using Residual Analysis, ANOVA, and FFT Analysis - Kormil Saputra; Ika Umratul Asni Aminy; Rahmatun Inayah (Tinta Emas Publisher, 2026)
Understanding the periodic behavior of air temperature is essential for identifying local climatic dynamics, particularly in island regions where topography, coastal influence, and land–sea interactions may generate spatially heterogeneous thermal patterns. This study successfully characterized the periodic dynamics of air temperature across four regions of Lombok Island, Indonesia, namely Labuhan Lombok, Bayan, Lembar, and Kuta. A quantitative time-series approach was applied using hourly air temperature observations, which were analyzed through sine fitting, residual analysis, analysis of variance (ANOVA), and Fast Fourier Transform (FFT). The ANOVA results confirmed that the sine wave model was statistically significant in all observation regions, with p-values below 0.0001, indicating the strong presence of periodic temperature behavior. Bayan produced the highest F-value, followed by Labuhan Lombok, suggesting stronger model suitability in these regions, while Lembar and Kuta remained statistically significant despite exhibiting more moderate periodic model strength. Residual analysis showed that the sine model effectively captured the dominant daily temperature cycle, although several short-term local fluctuations were not fully represented by a single harmonic function. The FFT results further revealed a dominant frequency component in all regions, confirming that air temperature variability in Lombok is primarily governed by a diurnal cycle. Overall, the findings demonstrate that temperature periodicity across Lombok differs spatially in terms of mean temperature, fluctuation amplitude, model fitness, and dominant frequency characteristics. This study provides a quantitative basis for local climate characterization and supports future microclimate assessment, environmental monitoring, and region-specific climate adaptation planning in island environments.